2022
DOI: 10.3390/diagnostics12020523
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Point Shear Wave Elastography (pSWE) Using Acoustic Radiation Force Impulse (ARFI) Technology in Mesenteric Masses: A Feasibility Study

Abstract: Purpose: To evaluate the diagnostic performance of ultrasound point shear wave elastography (pSWE) using acoustic radiation force impulse (ARFI) technology in different benign and malignant mesenteric masses (MMs). Methods: A total of 69 patients with MMs diagnosed from September 2018 to November 2021 were included retrospectively in the study. The inclusion criteria were (1) an MM over 1 cm; (2) valid ARFI measurements; and (3) confirmation of the diagnosis of an MM by histological examination and/or clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…These observations are contrary to neoplastic lesions in other organs, where the stiffness of malignant lesions is often higher than that of benign lesions and the surrounding parenchyma [13,[17][18][19]. It is unclear why, in the spleen, as shown in the current study, the stiffness of the FSLs was lower than that of the surrounding NSP.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…These observations are contrary to neoplastic lesions in other organs, where the stiffness of malignant lesions is often higher than that of benign lesions and the surrounding parenchyma [13,[17][18][19]. It is unclear why, in the spleen, as shown in the current study, the stiffness of the FSLs was lower than that of the surrounding NSP.…”
Section: Discussioncontrasting
confidence: 86%
“…US elastography represents a good, non-invasive method for characterizing tissue stiffness with various applications in many organs, including the liver, thyroid, pancreas, kidney, breast, lymph nodes, and prostate [13]. In previous studies, we have shown the feasibility and diagnostic performance of ARFI elastography in differentiating benign from malignant pathologies in the mesentery [17], omentum [18], and lung [19]. There are guidelines regarding the implementation of spleen elastography in patients with liver disease to assess for liver fibrosis, clinically relevant portal hypertension, and the presence of esophageal varices [13].…”
Section: Discussionmentioning
confidence: 99%
“…If the lesion moved while being measured, this single reading “shot” was considered invalid and was repeated. A total of 11 valid measurements were obtained for each ARFI study 14 15 18. ARFI study was considered valid only if the success rate to obtain 11 measurements was >60%.…”
Section: Methodsmentioning
confidence: 99%
“…US elastography is a non-invasive imaging technique for the assessment of tissue stiffness with current established guidelines for hepatic and non-hepatic applications 12–15. Acoustic radiation force impulse (ARFI) is a type of point shear wave elastography (pSWE) which depends on the differences of acoustic wave propagation velocity in different tissues determined by measuring the degree of displacement within a 0.5–1.0 cm box on the US screen, known as ‘region of interest’ (ROI) 16…”
Section: Introductionmentioning
confidence: 99%
“…Так, в многочисленных исследованиях было показано, что при случайно обнаруженных мезентериальных патологиях ARFI в сочетании с особенностями УЗИ в B-режиме (TUS) и паттернами изменения перфузии при CEUS может помочь в разработке диагностических алгоритмов. Однако при наличии злокачественного заболевания или клинического подозрения на злокачественное заболевание брыжейки КТ с контрастированием, ПЭТ-КТ и биопсия с гистологической верификацией продолжают оставаться методом визуализации с наивысшей диагностической эффективностью [88,89].…”
Section: инструментальная диагностикаunclassified